Efficacy of EDTA-T gel for smear layer removal at root surfaces - Carvalho Batista, Luiz Henrique [UNESP]; Cezar Sampaio, José Eduardo [UNESP]; Pilatti, Gibson Luiz; Shibli, Jamil Awad (My University, 2005)
Objective: The purpose of this in vitro study was to investigate the efficacy of EDTA gel preparation, associated with texapon detergent (EDTA-T), for removing the smear layer at human root surfaces. Method and materials: An experimental smear layer was produced by scaling using periodontal curettes, and the root surfaces were etched with the following concentrations of EDTA-T: 5%, 10%, 15%, 20%, 24%, and negative control (saline solution) for 1, 2, or 3 minutes using both passive and active methods. The surfaces were evaluated by scanning electron microscopy, and photomicrographs were evaluated in relation to smear removal. Results: All EDTA-T groups were more effective than the control group (P < .0001). EDTA-T at 15% was more effective when applied by the passive method, although this difference was not observed for the active method. The active method was statistically better than the passive method (P < .0001). Conclusion: The etching of the root surface with EDTA-T gel by active application, independently of the other factors evaluated, was effective for smear layer removal.
Keywords: EDTA; Periodontal diseases; Periodontal therapy; Scanning electron microscopy; Smear layer; Tooth root; edetic acid; sodium chloride; texapon; concentration (parameters); controlled study; dental acid etching; dental equipment; dental surgery; experiment; gel; human; human tissue; in vitro study; intermethod comparison; microphotography; periodontics; scanning electron microscopy; smear; statistical analysis; time; tooth root; Acid Etching, Dental; Chelating Agents; Dentin; Edetic Acid; Gels; Humans; Microscopy, Electron, Scanning; Root Canal Preparation; Smear Layer; Time Factors; Tooth Root